Effectiveness of the Let’s Move It multi-level vocational school-based intervention on physical activity and sedentary behavior: a cluster randomized trial - Hankonen, Nelli; Haukkala, Ari; Palsola, Minttu; Heino, Matti Toivo Juhani; Sund, Reijo; Tokola, Kari; Absetz, Pilvikki; Araújo-Soares, Vera; Sniehotta, Falko F.; Borodulin, Katja; Uutela, Antti; Lintunen, Taru; et al. (Annals of behavioral medicine, 2025)
Low levels of physical activity (PA), more prevalent among those with low education, require effective interventions. Fewer trials have tested interventions to decrease sedentary behavior (SB). No school-based interventions have shown lasting effects on PA or SB in vocational schools.To examine whether the Let’s Move It intervention has effects on behavioral and clinical outcomes among vocational students after 2 and 14 months.A cluster randomized trial in 6 school units in vocational education in Finland (N = 1112) (mean age 18.5 years, range 15-46). The multi-component intervention targeted in-class activity opportunities (eg, teacher-led activity breaks, equipment in classrooms), and students’ motivation and self-regulation (eg, 6 group sessions, à 45-60 min, during the intensive intervention period of 2 months). Valid (≥ 4 days, ≥ 10 h/day) accelerometer data were obtained from 741 students at baseline, 521 (70.3%) at 2 months, and 406 (54.8%) at 14 months.No evidence of a significant intervention effect on the co-primary outcomes (moderate-to-vigorous PA, SB, breaks in SB) was found. Participants in the intervention arm reduced their total daily SB time by 32 min (95% CI, −43.2 to −20.8) on weekdays, compared with the control arm’s reduction of 8.6 (95% CI, −19.5 to 2.3) and engaged in more accelerometer-measured light PA during school time. Few differences were found in secondary outcomes. The fidelity of intervention delivery was relatively good.This school-based intervention did not affect leisure-time activity. Despite a positive outcome on school-time light PA, more comprehensive or intensive environmental changes may be needed to meaningfully improve vocational students’ total activity.On average, people with vocational education are less physically active than those with higher education. Interventions conducted in vocational schools have not been able to report lasting effects on physical activity or sedentary behavior. This study examined whether the Let’s Move It intervention can improve vocational school students’ activity behaviors and body composition, measured after 2 and 14 months. To test the impact of this intervention, we allocated 6 school units in Finland to either the intervention group or the control group, which received no intervention. A total of 1112 students participated. The intervention aimed to increase students’ opportunities for in-class activity (eg, teacher-led activity breaks and providing equipment in classrooms) and improve students’ motivation and self-regulatory skills (eg, by offering 6 group sessions on these topics over the course of 2 months). The intervention did not change students’ overall physical activity. However, after 2 months, students in the intervention schools had less sedentary time on weekdays and engaged in more light activity during school hours, compared to students in the control schools. Despite this positive influence on school-time activity, more intensive changes to the environment may be needed to substantially improve vocational students’ overall physical activity levels.